Maternal influence on early lipid content in an introduced partially anadromous population of rainbow trout Oncorhynchus mykiss - Liberoff, Ana Laura (2019)
This study evaluated how the maternal migratory tactic in a partially anadromous population of Oncorhynchus mykiss may influence the early energetic status of their offspring. Total lipid content variation (% dry mass) of recently emerged fry caught in the Santa Cruz River, Argentina, was evaluated as a function of their maternal origin (anadromous v. resident) and fork length (LF ). Lipid content of fry decreased with LF and was higher for offspring of anadromous mothers.